Forms of Learner Ill-Discipline Prevalent in Grade 10 Classes: A Qualitative Case Study in a South African Secondary School - Habasisa Molise; Nkarhi Mathebula (Research and Innovation in Social Science Education Journal (RISSEJ), 2026)
A persistent Problem facing South African secondary learners today is still learner ill-discipline, which under-mines the effectiveness of teaching and learning. This qualitative case study investigated the forms of learner ill-discipline existing in Grade 10 classes at a particular high school in South Africa. A total of eight people participated in the inquiries, including six Grade 10 students from the school because of which this study took place, a subject teacher, and the principal. To generate data, semi-structured interviews were conducted with the school principal, teachers, and students. In addition, non-participant observations were made in class and outside. It was found that the prevailing forms of learner ill-discipline were many, including late-coming and absenteeism, improper dressing, use of cell phones during lessons, refusal to do one's homework and lack of academic responsibility, and disruption in class. Such conduct was found to rob instructional time, weaken learner engagement and challenge teacher–learner relations. The findings are consistent with prior studies by others that document truancy, interference in the classroom and school rules were central disciplinary problems in secondary education. The study concludes that in Grade 10 ill-discipline among learners reflects several incompatible elements, but echoing one another at school as well as among learners. This kind of situation demands our attention in action, teaching approaches and policy direction.